Emakumearen irudia euskaltzaindiaren hiztegian - Landa Torre, Esther (Huarte de San Juan. Filología y Didáctica de la Lengua, 2014)
Although the Basque language is not a gender language, it reflects the characteristics and values of our patriarchal and androcentric society; moreover, it does not only reflect them, it also transmits and perpetuates them. Aim: to analyze roles, and prototypes of woman and man that are presented in Euskaltzaindiaren Hizegia and their statistical differences. It should be mentioned that the present study is the first quantitative study, an approach to what would be a full analysis, so the sample used does not contain all the susceptible words of Euskaltzaindiaren Hiztegia that can be studied. Results: The results showed that the treatment of women and men given in this dictionary is not equal. We can also say that the experience of women, their jobs, features, etc. appear in many fewer occasions than man´s ones. At the same time, the number of examples used to express the female words and those used for expressing male ones is not balanced. The differences are evident and the gap between the two genders is growing as the analysis becomes more specific, more concrete.